Structural behavior of out-of-plane loaded precast lightweight EPS-foam concrete C-shaped slabs - Saheed, Sanusi; Mugahed Amran, Y. H.; El-Zeadani, Mohamed; A. Aziz, Farah Nora; Fediuk, Roman; Alyousef, Rayed; Alabduljabbar, Hisham (Elsevier, 2021)
This study aimed to develop optimum lightweight expanded polystyrene foam (LEPSF) concrete with a compressive strength of 35 MPa at a density of 1980 kg/m3, to produce precast LEPSF concrete C-shaped slabs with different parameters. LEPSF beads and quarry dust were used as partial replacements for coarse and fine aggregates at different percentages of (15%, 22.5%, and 30%) and (7.5%, 15%, and 22.5%), respectively. From the findings of this investigation, it was noticed that the use of LEPSF beads resulted in acceptable early age strength; however, a reduction in strength was observed at a mature age. Meanwhile, the use of quarry dust improved the compressive strength of LEPSF concrete by more than 30% compared to the mixtures with EPS alone. Totally, 256 samples were prepared to examine the physical and engineering properties of LEPSF concrete mixtures. Results revealed that the deflection of the full-scale LEPSF concrete C-shaped slabs was 31.5%–45.7% more than that recorded in comparable normal concrete slabs. Meanwhile, results have shown that the ductility of the precast LEPSF concrete C-shaped slabs improved in comparison to the normal concrete samples and they also exhibited 20% reduction in the self-weight. It was also seen that precast LEPSF concrete C-shaped slabs give more warning time before failure occurs. As such, it was concluded that the developed precast LEPSF concrete C-shaped slabs have a significant potential to be adopted in flooring systems of modern buildings today.